Evidence-based Research in Complementary and Alternative Medicine I: History - Chiappelli, Francesco (Oxford University Press, 2005)
Contemporary Western medicine has witnessed a fragmentation of our conceptualization of the medical endeavor into ‘traditional medicine’ and ‘non-traditional medicine’. The former is meant to refer to the Western medical tradition, the latter encompasses both ‘complementary’ and ‘alternative’ medical practices. Complementary medicine complements conventional medical treatments, and alternative modes of medical interventions are meant to replace traditional Western medicine. Evidence-based research must be directed at establishing the best available evidence in complementary and alternative medicine. This paper is the first of a set of four ‘lectures’ that reviews the process of evidence-based research, and discusses its implications and applications for the early decades of the 21st century. The purpose of this paper is to introduce the series by examining some of the historical and philosophical foundations of this research endeavor.